A checklist of the chinese species of the family Perlidae (Plecoptera: Perloidea) - Du, Yuzhou (Acta entomologica slovenica (Ljubljana), 1999)
Examination of numerous collections and published records has resulted in a checklist of the family Perlidae from China. A total of 165 species representing two subfamilies and twenty genera is found in China. Eight new combinations, one synonym and seven species incertae sedis are proposed in this checklist.
Keywords: Kitajska; Plecoptera; zoogeografija; zoologija; zoology